STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI DALAM MENINGKATKAN HARD SKILL DAN SOFT SKILL SANTRI KOTA BATAM - Asep Ijudin; Muhammad Juni Beddu; Ita Tryas Nur Rochbani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic boarding schools face challenges in adopting technology for Islamic Religious Education (PAI) learning, even though technology can enhance the quality of education and students' skills. This study aims to analyze the implementation of technology based learning in Islamic boarding schools to improve students' hard skills and soft skills. The research method uses a qualitative approach with a case study design, involving observations, in-depth interviews, and document analysis in three boarding schools in Batam. The results show that technology effectively enhances students' hard skills in studying the Qur’an, fiqh, and Islamic history, as well as strengthens soft skills such as communication, leadership, and teamwork through digital based projects. Key supporting factors include leadership support, students' enthusiasm, and the availability of digital resources. Meanwhile, hindering factors include infrastructure limitations, varying teacher competencies, and resistance to change. The conclusion of this study suggests improvements in infrastructure, teacher training, and policies that support the integration of technology in PAI learning.